(untitled) - Barrass, Robert (London, 2002)
This book, by a scientist, will help reader to write: to observe, remember, think and plan; to manage your time and avoid stress; and to improve your communication skills. Extensively revised and updated, this valuable reference takes into account the huge changes in information technology since the very successful first edition
Sinh hoạt học thuật DT&CGCT,Thống kê ứng dụng và viết báo cáo khoa học
Keywords: Technical writing,Viết trong kỹ thuật